Combined Effect of Magnetic Field and Compressibility on Rayleigh Taylor Instability - Mitra, Aniruddha; Mandal, Labakanta; Roychoudhury, Rajkumar; Khan, Manoranjan (Scientific Research, 2015)
The nonlinear analysis of the combined effect of magnetic field and compressibility on the growth rate of Rayleigh-Taylor (RT) instability has been investigated for inviscid two fluid interface. We have considered an interface-parallel density dependent magnetic field and used Layzer’s approach to analyze the problem. We have also investigated the relative effect of magnetic pressure and hydrodynamic pressure on RT instability through the variation of the ratio of hydromagnetic pressure to magnetic pressure ( β ). Dynamics of bubble and spike has been studied analytically and numerically. Finally, we have obtained the stability conditions of our result through linear stability analysis
Keywords: Rayleigh-Taylor Instability; Bubbles; Spikes; Self Generated Magnetic Field; Compressibility; Density Dependent Magnetic Field; ICF